Maternal Neu5Ac Supplementation During Pregnancy Improves Offspring Learning and Memory Ability in Rats - Bian, DongSheng; Wang, Xinyue; Huang, Jiale; Chen, Xiaoxuan; Li, Hongwei (Frontiers in Nutrition, 2021)
Sialic acids are postulated to improve cognitive abilities. This study aimed to evaluated the effects of sialic acid on behavior when administered in a free form as N-acetylneuraminic acid (Neu5Ac) to the pregnant mothers or rat pus. Forty male 21-day-old rat pups and twenty 15-day-pregnant rats were randomized into four Neu5Ac treated groups: 0 (control), or 10 mg/kg, 20 mg/kg, and 40 mg/kg. Morris water maze test and shuttle box test were performed on the rat pups and maternal Neu5Ac-supplemented offspring on day 100 to evaluate their cognitive performance. The Neu5Ac levels in the cerebral cortex and hippocampus were tested with high performance liquid chromatographyfluorescence detection. We found that the maternal Neu5Ac-supplemented offspring showed better cognitive performance, less escape latency in the Morris water maze test and less electric shock time shuttle box test, compared with the untreated control. In the meantime, the Neu5Ac level in offspring’s cerebral cortex and hippocampus was higher in the Neu5Ac treatment group than that in the untreated control group. However, no significant differences were observed between rat pups in the treated and the untreated control groups in terms of cognitive performance and Neu5Ac content in the cerebral cortex and hippocampus. Maternal Neu5Ac supplementation during pregnancy could effectively promote offspring’s brain Neu5Ac content and enhance their cognitive performance but Neu5Ac had no such effect on rat pups while directly supplemented with Neu5Ac.